Biomedical signal and image processing - Najarian, Kayvan (Boca Raton : Taylor & Francis/CRC Press, 2012)
"Preface The first edition of the book Biomedical Signal and Image Processing was published by CRC Press in 2005. It was used by many universities and educational institutions as a textbook for upper undergraduate level and first year graduate level courses in signal and image processing. It was also used by a number of companies and research institutions as a reference book for their research projects. This highly encouraging impact of the first edition motivated me to look into ways to improve the book and create a second edition. The second edition you have in hand has the following improvements compared to the first edition: - A number of editorial corrections have been made to address the typos, grammatical errors, and ambiguities in some mathematical equations. - Many examples have been added to almost all chapters, of which the majority are MATLABʼ examples, further illustrating the concepts described in the text. - Further explanations and justifications have been provided for some signal and image processing concepts that may have needed more illustration. Finally, I would like to thank all the people who contacted me and my coauthor, Dr. Splinter, and shared with us their thoughts and ideas regarding this book. I hope that you find the second edition even more useful than the first one! Kayvan Najarian Virginia Commonwealth University Richmond, Virginia For MATLABʼ and Simulinkʼ product information, please contact: The MathWorks, Inc. 3 Apple Hill Drive Natick, MA, 01760-2098 USA Tel: 508-647-7000 Fax: 508-647-7001 E-mail: info@mathworks.com Web: www.mathworks.com"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Image Processing, Computer-Assisted.; Signal Processing, Computer-Assisted.